New Conditions for Obtaining the Exact Solutions of the General Riccati Equation - Lazhar Bougoffa (The Scientific World Journal)
We propose a direct method for solving the general Riccati equation y′=f(x)+g(x)y+h(x)y2. We first reduce it into an equivalent equation, and then we formulate the relations between the coefficients functions f(x),g(x), and h(x) of the equation to obtain an equivalent separable equation from which the previous equation can be solved in closed form. Several examples are presented to demonstrate the efficiency of this method.